Heredity and gene mapping of a novel white stripe leaf mutant in wheat - Hui-juan LI; Zhi-xin JIAO; Yong-jing NI; Yu-mei JIANG; Jun-chang LI; Chao PAN; Jing ZHANG; Yu-long SUN; Jun-hang AN; Hong-jie LIU; Qiao-yun LI; Ji-shan NIU (Journal of Integrative Agriculture)
Spotted leaf (spl) mutant is a type of leaf lesion mimic mutants in plants. We obtained some lesion mimic mutants from ethyl methane sulfonate (EMS)-mutagenized wheat (Triticum aestivum L.) cultivar Guomai 301 (wild type, WT), and one of them was named as white stripe leaf (wsl) mutant because of the white stripes on its leaves. Here we report the heredity and gene mapping of this novel wheat mutant wsl. There are many small scattered white stripes on the leaves of wsl throughout its whole growth period. As the plants grew, the white stripes became more severe and the necrotic area expanded. The mutant wsl grew only weakly before the jointing stage and gradually recovered after jointing. The length and width of the flag leaf, spike number per plant and thousand-grain weight of wsl were significantly lower than those of the WT. Genetic analysis indicated that the trait of white stripe leaf was controlled by a recessive gene locus, named as wsl, which was mapped on the short arm of chromosome 6B by SSR marker assay. Four SSR markers in the F2 population of wsl×CS were linked to wsl in the order of Xgpw1079-Xwmc104-Xgwm508-wsl-Xgpw7651 at 7.1, 5.2, 8.7, and 4.4 cM, respectively and three SSR markers in the F2 population of wsl×Jimai 22 were linked to wsl in the order of Xgwm508-Xwmc494-Xgwm518-wsl at 3.5, 1.6 and 8.2 cM, respectively. In comparison to the reference genome sequence of Chinese Spring (CS), wsl is located in a 91-Mb region from 88 Mb (Xgwm518) to 179 Mb (Xgpw7651) on chromosome 6BS. Mutant wsl is a novel germplasm for studying the molecular mechanism of wheat leaf development.